-(-7+1)=-(-3-8q)

Simple and best practice solution for -(-7+1)=-(-3-8q) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-7+1)=-(-3-8q) equation:


Simplifying
-1(-7 + 1) = -1(-3 + -8q)

Combine like terms: -7 + 1 = -6
-1(-6) = -1(-3 + -8q)

Multiply -1 * -6
6 = -1(-3 + -8q)
6 = (-3 * -1 + -8q * -1)
6 = (3 + 8q)

Solving
6 = 3 + 8q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-8q' to each side of the equation.
6 + -8q = 3 + 8q + -8q

Combine like terms: 8q + -8q = 0
6 + -8q = 3 + 0
6 + -8q = 3

Add '-6' to each side of the equation.
6 + -6 + -8q = 3 + -6

Combine like terms: 6 + -6 = 0
0 + -8q = 3 + -6
-8q = 3 + -6

Combine like terms: 3 + -6 = -3
-8q = -3

Divide each side by '-8'.
q = 0.375

Simplifying
q = 0.375

See similar equations:

| 8*(2x+1)-(11-2)*x=6 | | x-7y=-14 | | 0=14t^2+16t+1798 | | 6[x-2(2x+3)+1]+3(5+6x)+x=0 | | 1.76=a-2.84 | | x+x-2+x+1=62 | | 8x^2-4x-60=0 | | 6x-14=6x+6-3x | | 10+2x=328 | | 6x-14=8x+8-3x | | 6x-14=5x+5-3x | | 7x-2=-3x | | 2w^2-3w-90=0 | | 5n-2=3n+6 | | 2a-[(3a+4)-5]-a=5 | | 19+7n-5+6n=8n+7+3n-19 | | (x+126)(x+120)=0 | | 2(5g-3)-6(g-7)=g+6(g+7) | | 10y-20=-4y+6 | | 4y-2+3=-2y-4 | | -4(7n-4)+4n= | | 11-(7a-a)+11a=4(3a+7) | | 20(31)= | | 8x-11y=32 | | 2y+5x=6 | | x+494=2753 | | 3(8n-2)-3(1-n)+8=8 | | 2x+2j=1-yj | | 5[x-4(4x-5)]=3-2x | | 3y+7=16 | | (2-4j)x+9+(1+4j)=0 | | -3n-2+6n=7n+26 |

Equations solver categories